Local adaptation (local versus foreign) in ciliate microcosms experiment - Staffan Jacob; Delphine Legrand; Alexis S Chaine; Dries Bonte; Nicolas Schtickzelle; Michèle Huet; Jean Clobert (PANGAEA, 2017)
“Local versus foreign” estimation of local adaptation (growth rate at 35°C of individuals from experimental populations at 35°C that received immigrants minus the growth rate at 35°C of individuals originating from control populations without immigration and maintained at 23°C). Gene_flow_treatment = types of gene flow, with or without habitat choice. Gene_flow_level = level of dispersal toward the focal population (10% or 30% of the local population extquotesingle initial carrying capacity). Local_adaptation_LvsF = growth rate at 35°C of individuals from experimental populations at 35°C that received immigrants minus the growth rate at 35°C of individuals originating from control populations without immigration and maintained at 23°C. Time: initial = initial measurement, before the first dispersal event; final = measured at the end of the experiment (6 weeks)
In supplement to: Jacob, S et al. (2017): Gene flow favours local adaptation under habitat choice in ciliate microcosms. Nature Ecology & Evolution, 1(9), 1407-1410, https://doi.org/10.1038/s41559-017-0269-5